Идентификация побочных продуктов реакции взаимодействия тиомочевины с глиоксалем - Каличкина, Людмила Евгеньевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In the present work, we studied the reaction of thiourea with glyoxal in water by HPLC and NMR methods. Kinetic curves of thiourea and 4,5-dihydroxyimidazoldin-2-thione reaction were obtained by HPLC method. Byproducts such as 2-thioimidazole and cis-, trans- 4,5-dihydroxyimidazoldin-2-one for reaction of thiourea with glyoxal have been identified by means NMR (DEPT 135, 13C-1H HSQC, 13C-1H HMBC) methods. The scheme of reactions explaining formation of byproducts has been proposed - DHIT reacts with thiourea to form 2-thioimidazole and urea, which, in turn, interacts with glyoxal to form 4,5- dihydroxyimidazoldin-2-one.